Fiqh al-Muʾassasāt in Contemporary Muslim Society: A Socio-Political Analysis of the Establishment of Indonesia’s Ministry of Hajj - M. Rizal Qosim; Dwi Surya Atmaja; Prihantono (Journal of Islamic Law, 2026)
The Ministry of Hajj was formally established as a governmental institution in Indonesia in September 2025, prompting critical inquiries and ongoing debates among the country’s Muslim community. Employing the theoretical lenses of governmentality and the maqāṣid al-sharīʿah (the higher objectives of Islamic law) framework, this study investigates the bureaucratization of the religious pilgrimage as articulated by the state within the broader context of governance and contemporary power structures. This institutionalization process simultaneously intensifies administrative oversight of religious practices, thereby generating tensions between normative protections and the rationalities characteristic of modern power. Through a qualitative socio-political analysis, the findings reveal that the hajj pilgrimage cannot be understood solely as an individual religious obligation; rather, it constitutes a state-led institutional project aimed at protecting pilgrims and promoting public welfare. In this capacity, the Ministry of Hajj operates as a maqāṣid agent, safeguarding pilgrims’ physical safety, financial security, dignity, and the proper performance of religious rituals through mechanisms grounded in public law. Theoretically, this article contributes by advancing a novel interpretation of istiṭāʿah (capability) as a social construct conditioned and mediated by the state, and by proposing fiqh al-muʾassasāt (institutional fiqh) as an analytical framework for understanding the operationalization of Islamic legal norms within contemporary governance structures. This study enriches socio-political scholarship in Islamic studies by elucidating the dynamic relationship among religion, the state, and citizens in the governance of mass religious practices in contemporary Muslim societies. [Kementerian Haji secara resmi dibentuk sebagai lembaga pemerintahan di Indonesia pada September 2025, yang memunculkan berbagai pertanyaan kritis dan perdebatan berkelanjutan di kalangan umat Islam di tanah air. Dengan bertumpu pada konsep governmentality (pemerintahan) dan kerangka maqāṣid al-sharīʿah (tujuan hukum Islam), penelitian ini mengkaji proses birokratisasi ibadah haji sebagaimana dirumuskan oleh negara dalam konteks tata kelola pemerintahan dan struktur kekuasaan modern. Proses institusionalisasi ini secara bersamaan memperkuat pengawasan administratif terhadap praktik-praktik keagamaan, sekaligus melahirkan ketegangan antara perlindungan normatif dan rasionalitas yang melekat dalam kekuasaan modern. Melalui analisis kualitatif sosio-politik, temuan penelitian menunjukkan bahwa ibadah haji tidak lagi dapat dipahami semata-mata sebagai kewajiban keagamaan individual, melainkan sebagai proyek institusional yang dipimpin oleh negara dengan tujuan menjamin perlindungan jemaah dan mendorong kemaslahatan publik. Dalam konteks ini, Kementerian Haji berfungsi sebagai agen maqāṣid yang berperan menjaga keselamatan fisik, keamanan finansial, martabat, serta ketertiban pelaksanaan ritual keagamaan para jemaah melalui mekanisme kebijakan publik. Secara teoretis, artikel ini berkontribusi dengan mengajukan tafsir baru atas konsep istiṭāʿah (mampu) sebagai konstruksi sosial yang dikondisikan dan dimediasi oleh negara, serta dengan menawarkan fiqh al-muʾassasāt (fikih politik kelembagaan Islam) sebagai kerangka analitis untuk memahami operasionalisasi norma-norma hukum Islam dalam struktur tata kelola pemerintahan kontemporer. Studi ini memperkaya kajian sosio-politik dalam studi Islam dengan menjelaskan relasi dinamis antara agama, negara, dan warga negara dalam pengelolaan praktik-praktik keagamaan massal di masyarakat Muslim kontemporer.]